Vitamin B12, Folate, Homocysteine, and Bone Health in Adults and Elderly People: A Systematic Review with Meta-Analyses - J. P. van Wijngaarden; E. L. Doets; A. Szczecińska; O. W. Souverein; M. E. Duffy; C. Dullemeijer; A. E. J. M. Cavelaars; B. Pietruszka; P. van't Veer; A. Brzozowska; R. A. M. Dhonukshe-Rutten; C. P. G. M. de Groot (Journal of Nutrition and Metabolism)
Elevated homocysteine levels and low vitamin B12 and folate levels have been associated with deteriorated bone health. This systematic literature review with dose-response meta-analyses summarizes the available scientific evidence on associations of vitamin B12, folate, and homocysteine status with fractures and bone mineral density (BMD). Twenty-seven eligible cross-sectional (n=14) and prospective (n=13) observational studies and one RCT were identified. Meta-analysis on four prospective studies including 7475 people showed a modest decrease in fracture risk of 4% per 50 pmol/L increase in vitamin B12 levels, which was borderline significant (RR = 0.96, 95% CI = 0.92 to 1.00). Meta-analysis of eight studies including 11511 people showed an increased fracture risk of 4% per μmol/L increase in homocysteine concentration (RR = 1.04, 95% CI = 1.02 to 1.07). We could not draw a conclusion regarding folate levels and fracture risk, as too few studies investigated this association. Meta-analyses regarding vitamin B12, folate and homocysteine levels, and BMD were possible in female populations only and showed no associations. Results from studies regarding BMD that could not be included in the meta-analyses were not univocal.